Assessment of facial nerve injury using Deep Subfascial approach to Temporo-mandibular joint - Kumar, Ankit; Kumar, Sourav; Khan, Musaab; Nayak, Dipti; Sharma, Ashish; Tripathi, Siddhi (Asian Journal of Medical Sciences, 2021)
Background: Surgical access to the temporomandibular joint (TMJ) and zygomatic arch is a challenge even to the experienced maxillofacial surgeon. The conventional subfascial approach to these structures carries the potential risk of transient paralysis of the frontalis and orbicularis oculi muscles. The deep subfascial approach provides an additional layer of protection (the deep layer of the temporalis fascia and the superficial temporal fat pad) to the temporal and zygomatic branches of the facial nerve and thus, is the safest method to avoid facial nerve injury. Aims and Objective: To assess facial nerve injury (FN) following TMJ surgery using deep Subfascial approach and measuring it on House and Brackman facial nerve grading system (HBFNGS). Materials and Methods: A randomized study was performed from August 2013 to March 2017 on 24 patients with unilateral and bilateral TMJ ankylosis. All patients were evaluated objectively for facial nerve injury using with house and brackmann facial nerve injury grading system post-operatively and subjectively inthe various time periods, i.e. 24 hours, 1 week, 1month, 3 months and 6 months. Results: Brackmann facial nerve grading system at 24 hours post operatively– in the deep subfascial approach group, 91.7% of patients (23 cases) had Grade 1 injury and 8.3% (1case) had Grade 3 injury. The condition improved with time with full recovery of facial nerve injury (FN) at all surgical sites at 6 months. Conclusion: The deep subfascial approach has a distinct advantage over the conventional approaches when dissecting the temporal region and is thesafest method to avoid injury to facial nerve injury (FN).